Comparative Evaluation of the Efficiency of Regulatory Mechanisms of the Oil and Gas Industry and Industrial Waste Processing - SATENOVA, Dinara Yerbolovna; BULAKBAY, Zhanat Mukhanbetzhankyzy; AZYLKANOVA, Saule; BERSTEMBAEVA, Rysty Kudaibergenovna; ABYLKASSIMOVA, Zhibek; SEITKHOZHINA, Jamilya (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.11.7(47).15, 2020)
Many forecasts agree that the volume of the world oil production will soon peak and then begin to decline. Other studies conclude that stocks oils are not running out, they are becoming less available. The future is uncertain, it is impossible to plan it precisely. Nevertheless, this industry is one of the most profitable in the Republic of Kazakhstan, where oil production is constantly increasing, all regulatory mechanisms are in place, and although their effectiveness is not assessed high, however, a mechanism for interaction with all sectors of the economy has been established. Major problems were found in the regulatory and environmental management of the oil industry; however, it can be noted that in the processing industry of manufactured enterprises there is no interaction with many sectors of the economy. The authors proposed to compare the effectiveness of regulatory mechanisms in the oil and gas industry and in the industry of processing of industrial waste. Subsequently, it was revealed that the mechanisms for regulating the industrial waste processing industry were practically not developed, and the problems arising in this industry ignored by government agencies. In this way, avoiding the problems of the industrial waste processing industry brings Kazakhstan to environmental disaster.